Quantitative sonographic assessment of quadriceps muscle thickness for fall injury prediction in patients undergoing maintenance hemodialysis: an observational cohort study - Asuka Sai (BMC Nephrology, 2021)
Abstract Background Accidental fall risk is high in patients undergoing maintenance hemodialysis. Falls are associated with fatal injury, comorbidities, and mortality. Risk assessment should be a primary component of fall prevention. This study investigated whether quadriceps muscle thickness measured using ultrasonography can predict fall injury among dialysis patients. Methods Using an observational cohort study design, 180 ambulatory hemodialysis patients were recruited from 2015 to 2016 from four dialysis clinics. The sum of the maximum quadriceps muscle thickness on both sides and the average of the maximum thigh circumference and handgrip strength after hemodialysis were calculated. Patients were stratified according to tertiles of quadriceps muscle thickness. Fall injury was surveyed according to the patient’s self-report during the one-year period. Results Among the 180 hemodialysis patients, 44 (24.4%) had fall injuries during the 12-month follow-up period. When the quadriceps muscle thickness levels were stratified into sex-specific tertiles, patients in the lowest tertile were more likely to have a higher incidence of fall injury than those in the higher two tertiles (0.52 vs. 0.19 and 0.17 fall injuries/person-year). After adjusting for covariates, lower quadriceps muscle thickness was found to be an independent predictor of fall injury (hazard ratio [95% confidence interval], 2.33 [1.22–4.52], P < 0.05). Receiver operating characteristic curves were constructed to determine the optimal cutoffs of quadriceps muscle thickness, thigh circumference, and handgrip strength that best predicted fall injury (quadriceps muscle thickness, 3.37 cm and 3.54 cm in men and women; thigh circumference, 44.6 cm and 37.2 cm in men and women; and handgrip strength, 23.3 kg and 16.5 kg in men and women). Using these cutoff values, the areas under the curve were 0.662 (95% CI, 0.576–0.738), 0.625 (95% CI, 0.545–0.699), and 0.701 (95% CI, 0.617–0.774), for quadriceps muscle thickness, thigh circumference, and handgrip strength, respectively. Quadriceps muscle thickness was a more precise predictor of fall injury than thigh circumference and had similar diagnostic performance as handgrip strength tests in dialysis patients. Conclusions Quadriceps muscle thickness can be measured easily at the bedside using ultrasonography and is a precise predictor of fall injury in patients undergoing maintenance hemodialysis.